WHETHER BOOK TAX DIFFERENCES AFFECT THE PRICE BOOK VALUE? - Ranatarisza M.M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2018)
The objective of the study was to describe book tax different influence towards price book value. The study was an explanatory study with quantitative approach. The setting of the study was manufacturing companies listed in Indonesian Stock Exchange. The independent variables were book tax different which measured using temporary differences and book tax different measured by permanent differences. The dependent variable was price book value. The data analysis involved descriptive statistics, classical assumption test, multiple linear regression and hypothesis-testing using Statistical Package for Social Science 21.0. The findings were: temporary differences did not have significant influence towards price book value, meaning that increasing temporary differences would result in insignificant increase in price book value and was not the main determining factor of price book value; permanent differences had significant influence towards price book value, which mean increasing permanent differences would increase price book value and was the main determining factor in describing level of company’s price book value; there was significant, positive and simultaneous influence between temporary differences and permanent differences as the indicator of book tax different towards price book value in the companies.